Odrodzenie praktyki namaszczania chorych w niemieckim luteranizmie - Jacek Froniewski (Wrocławski Przegląd Teologiczny)
In catholic circles there is a rather common belief that Lutheran Churches do not practice the anointing of the sick. The source of such a belief is the teaching contained in the M. Luther works, where the sacramental nature of the anointing of the sick is categorically denied. In modern times however, and especially since the middle of the 20th century, in many Lutheran Churches we have been able to notice a come back to the anointment rite, seen as a form of service of the Church towards the sick testified in the New Testament. This process is also a fruit of the development of mutual ecumenical links. The paper presents this phenomenon within the German Lutheranism, where is has the longest history and rich liturgical forms. A detailed analysis of the development of the liturgical forms of the anointing of the sick in the Lutheran Churches of Germany since the 19th century leads to optimistic theological conclusions as to the ecumenical prospects in this domain.